2000
DOI: 10.1021/bi991938b
|View full text |Cite
|
Sign up to set email alerts
|

Role for the C-Terminus in Agonist-Induced μ Opioid Receptor Phosphorylation and Desensitization

Abstract: Determining which domains and amino acid residues of the mu opioid receptor are phosphorylated is critical for understanding the mechanism of mu opioid receptor phosphorylation. The role of the C-terminus of the receptor was investigated by examining the C-terminally truncated or point-mutated mu opioid receptors in receptor phosphorylation and desensitization. Both wild-type and mutated receptors were stably expressed in Chinese hamster ovary (CHO) cells. The receptor expression was confirmed by receptor radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 35 publications
3
58
0
Order By: Relevance
“…Our current mutational analysis indicated that at least in HEK293 cells Thr 370 and Ser 375 are the residues phosphorylated in the presence of agonist, whereas Thr 394 is the residue that is phosphorylated in Chinese hamster ovary cells (37). Considering that the T394A mutation did not completely block agonist-induced MOR phosphorylation in Chinese hamster ovary cells (37), other sites involved in receptor phosphorylation in this cell line need to be identified.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Our current mutational analysis indicated that at least in HEK293 cells Thr 370 and Ser 375 are the residues phosphorylated in the presence of agonist, whereas Thr 394 is the residue that is phosphorylated in Chinese hamster ovary cells (37). Considering that the T394A mutation did not completely block agonist-induced MOR phosphorylation in Chinese hamster ovary cells (37), other sites involved in receptor phosphorylation in this cell line need to be identified.…”
Section: Discussionmentioning
confidence: 82%
“…Thr 394 , Ser 353 , and Ser 369 have been shown to be important for the regulation of -opioid receptors (20,34,35), ␦-opioid receptors (18,19), and -opioid receptors (36), respectively, although phosphorylation of these residues has not been determined. Recently, a T394A mutation was shown to significantly block DAMGO-induced MOR phosphorylation to approximately 10% of the wild type receptor and impair receptor desensitization in Chinese hamster ovary cells (37), indicating that this residue is a phosphorylation site. However, in HEK293 cells, the mutation of Thr 394 to Ala reduced the DAMGO-induced phosphorylation level to approximately 80% of maximal phosphorylation obtained with wild type receptor (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Two research groups (14,21) . This discrepancy of identified phosphorylation sites in different cell lines may indicate that the agonist-induced phosphorylation sites are celltype specific.…”
Section: Resultsmentioning
confidence: 99%
“…The time course and dose-response relationships between phosphorylation and agonist-induced desensitization display parallels in CHO cells stably expressing MOR (13). The absence of agonist-induced phosphorylation by the mutation of putative phosphorylation sites to alanine completely blocks or significantly attenuates the agonist-induced receptor desensitization (14,15) and internalization (16). The enhanced phosphorylation of MOR has been correlated with the desensitization of MOR in thalamus of rats chronically treated with morphine (17).…”
mentioning
confidence: 99%
“…This suggests that the differences in MOR dephosphorylation rate are due to the agonist's ability to recruit ␤-arrestin1 to the receptor. Importantly, the possible continued phosphorylation of other residues cannot be discounted, including threonines 180 and 394, because both of these residues have been shown to be important for DAMGO-induced MOR desensitization (24,25). It is possible that the collective pattern of MOR phosphorylation will be critical in the overall functional state of the MOR.…”
Section: Discussionmentioning
confidence: 99%